Iowa Birdline update, February 10, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for February 10, 1992. The highlights for the update include sightings of a Slaty-backed Gull, Snowy Owl and a Gyrfalcon. Also included are handwritten notes with sightings of a gray phase Eastern Screech Owl looking out of a wood duck house and two Tundra Swans near Runnells. Epson - sheet feed/flatbed